Analisis Sistem Akuntansi Pembelian pada Toko Ritel Modern: Studi Kasus Indomaret: (Analysis of Purchasing Accounting System in Modern Retail Stores: Indomaret Case Study) - Az Zahro, Luthfi Alya; Febiona, Adra Olivia; Nadifa, Najwa Tyas; Pramesti, Ervy Agisti Ardhia; Maulana, Muhammad Akbar; Yuwono, Althanino Ligar (Indonesian Journal of Sustainability Policy and Technology, 2025)
Purpose: This study aims to analyze the implementation of the purchasing accounting system at a modern retail store, specifically Indomaret. The study focuses on how the system is applied in real-world operations, including the roles of various departments, procedures for restocking, document management, and internal control systems. Method: A qualitative descriptive approach was employed. Data were collected through direct interviews with the store manager of Indomaret in Medokan Ayu, Surabaya. The study used observational notes and documentation to explore how purchasing activities are carried out and recorded in practice. Findings: Indomaret applies a centralized and computerized purchasing system, involving strict functional separation between departments such as purchasing, warehouse, receiving, and accounting. The purchasing procedures follow two main channels: direct from suppliers and from distribution warehouses. Supporting documents such as delivery notes, purchase invoices, and inventory reports are systematically used. Real-time data entry through integrated systems ensures accuracy in recording. Internal control practices, including stock audits and tiered approvals, support operational effectiveness and security. Implications: The findings highlight the significance of combining digital accounting systems with strong internal controls in retail operations. The study provides practical insights for companies aiming to improve purchasing efficiency and control mechanisms, and it serves as a useful reference for accounting students and practitioners in the retail sector. Originality: This research offers a real-world examination of a centralized purchasing accounting system in a major retail chain. It contributes original insights into how theoretical models of internal control and accounting information systems are implemented in day-to-day retail operations. ABSTRAK: Tujuan: Penelitian ini bertujuan untuk menganalisis penerapan sistem akuntansi pembelian pada toko ritel modern, khususnya Indomaret. Fokus kajian mencakup peran tiap bagian, prosedur restock barang, pengelolaan dokumen, dan sistem pengendalian internal yang diterapkan. Metode: Penelitian ini menggunakan pendekatan kualitatif deskriptif. Data diperoleh melalui wawancara langsung dengan kepala toko Indomaret di Medokan Ayu, Surabaya, serta observasi dan dokumentasi untuk menggambarkan praktek nyata sistem akuntansi pembelian. Temuan: Indomaret menerapkan sistem pembelian yang terpusat dan terkomputerisasi dengan pemisahan fungsi yang jelas antara bagian gudang, pembelian, penerimaan, dan akuntansi. Prosedur pembelian dilakukan melalui dua jalur utama: langsung dari supplier dan dari gudang cabang. Dokumen pendukung seperti surat jalan, faktur, dan laporan stok digunakan secara sistematis. Proses pencatatan dilakukan secara real-time melalui sistem terintegrasi. Pengendalian internal dilakukan melalui audit stok harian dan sistem otorisasi berjenjang. Implikasi: Hasil penelitian menekankan pentingnya integrasi sistem akuntansi digital dengan pengendalian internal yang kuat dalam operasional ritel. Studi ini memberikan wawasan praktis bagi perusahaan yang ingin meningkatkan efisiensi pembelian dan sistem kontrol, serta menjadi referensi bagi akademisi dan praktisi. Orisinalitas: Penelitian ini menyajikan analisis nyata tentang penerapan sistem akuntansi pembelian terpusat di jaringan ritel besar. Penelitian ini memberikan kontribusi terhadap pemahaman implementasi sistem informasi akuntansi dalam praktik operasional sehari-hari. Kata Kunci: Sistem Pengendalian Internal, Toko Ritel Modern, Sistem Akuntansi Pembelian.